Dampak Implementasi Pembayaran Berbasis Kinerja (Pay-For-Performance) Pada Fasilitas Kesehatan Tingkat Pertama (FKTP) Terhadap Kualitas Layanan Kesehatan Di Berbagai Negara - Uswatun Khasanah; Mardiati Nadjib (Syntax Literate, 2023)
The pay-for-performance (P4P) mechanism is a strategy in the health sector to increase the availability, quality and utilization of health services. In P4P, incentives are given after achieving a series of agreed outcomes by improving the performance of health workers in health facilities. This literature review was conducted with the aim of knowing the impact of implementing pay-for-performance at primary care (FKTP) on the quality of health services in various countries. The method is carried out by searching several databases, namely Pubmed, Embase, and Proquest with the main intervention being the implementation of pay-for-performance. The results of the review focused on the impact of implementing pay-for-performance at First Level Health Facilities on the quality of health services in various countries. From this study it can be concluded that pay-for-performance has been used in various countries with different numbers and areas (domains) of indicators adapted to the characteristics of primary care in a country. Some of the benefits of implementing pay-for-performance are that it can stimulate quality improvement in clinical care and improve patient experience of the role of general practitioners and the system of care. P4P can improve the process and outcome of cardiovascular treatment. Providing incentives can have an effect on improving the quality of performance in clinical practice. Providing P4P incentives can meet the quality measures of hypertension care recommended by the guidelines. In the United States, the provision of P4P incentives can increase physician compliance to provide hypertension drugs according to guidelines. Providing incentives can also have an impact on improving blood pressure control in hypertensive patients.